Social impact and social performance of paddy rice production in Iran and Malaysia - Kalvani, Somayeh Rezaei; Sharaai, Amir Hamzah; Masri, Mohammad Firdaus; Mat Yunus, Nurul Faeiqah; Afendi, Mohd Ridzuan; Uchechukwu, Onyeiwu Brendan (Springer Nature, 2022)
Purpose: Sustainable agri-food production is incredibly important for society. Despite Iran and Malaysia being one of the highest production countries for paddy rice, there is no study on the social life cycle assessment (S-LCA) for rice production for both countries in the literature. The lack of data and complexity of social issue are the challenges of conducting the S-LCA study. This study compared the social impacts from the related stakeholders in the life cycle of paddy rice production between Malaysia and Iran. Methods: This study applied S-LCA based on UNEP (UNEP/SETAC Life Cycle Initiative, 2020) as an evaluation technique to investigate social issues and social performance of paddy rice production in Malaysia and Iran. This research included workers, local communities, and farmers as the stakeholders. The inventory data were collected by using questionnaires. The subcategories for evaluation were adapted from UNEP 2020 guideline. The items in the questionnaire were separately validated by experts in Malaysia and Iran, and the reliability was done by conducting pilot studies in Malaysia and Iran. The questionnaires were distributed by multistage sampling method. The following four steps were conducted following the ISO14040 framework: (1) goal and scope definition, (2) social life cycle inventory analysis (S-LCI), (3) social life cycle impact assessment (S-LCIA), and (4) interpretation. Results and discussion: The result showed that the social performance of workers and farmers in Malaysia was better than Iran because of low cost with high yield for farmers, contributing to increased income. Rice cultivation in Iran for local community did not show good performance regarding health and safety because of burning of rice residue. Around 62% of local Iranian people reported air pollution from rice residue burning. However, the overall social performance for local community was not different in Iran and Malaysia, showing good performances with respect to job opportunity. Sexual harassment was identified as one of the negative social issues in Iran with the score of 60%, including unwanted sexual attention. Moreover, the farmers showed poor performance in Iran, resulting from low satisfactory from income, and low yield and high cost of paddy production in Iran. Conclusion: The key investigation from this research revealed that social performance of crop production in different geographical areas could show different results. The key finding from this study reported that modern agriculture could increase social and economic performance by reducing the production cost, and increasing productivity and social performance in terms of satisfactory from income for farmers. The result of this study can be used for policy makers to improve social performance by using modern agriculture.